Immunization with plasmid DNA expressing Heat Shock Protein 40 confers prophylactic protection against chronic Toxoplasma gondii infection in Kunming mice - Li, Zhong-Yuan; Lu, Jing; Zhang, Nian-Zhang; Elsheikha, Hany M.; Hou, Jun-Ling; Guo, Hai-Ting; Zhu, Xing-Quan (2018)
Toxoplasma gondii causes one of the most common protozoal diseases of humans and animals worldwide. With the aim of designing an effective vaccine against T. gondii infection, we examined the immunogenicity of a DNA vaccine expressing heat shock protein 40 (HSP40) against challenge with T. gondii (type I RH and type II Pru) strains in Kunming mice. The plasmid pVAX1-HSP40 was constructed and used to immunize mice by intramuscular injection for three sequential immunizations with two-week intervals. This immunization regimen significantly reduced parasite cyst burden in pVAX1-HSP40-immunized mice (1871.9 ± 142.3) compared with control mouse groups immunized with pVAX1 (3479.2 ± 204.4), phosphate buffered saline (3024.4 ± 212.8), or left untreated (3275.0 ± 179.8) as healthy controls (p < 0.01). However, immunization failed to protect mice against challenge with the virulent RH strain. There was a significant increase in T lymphocyte subclasses (CD3e+CD4+ T and CD3e+CD8a+ T lymphocytes) in splenic tissues in immunized mice compared with controls (p < 0.05). However, the level of antibodies, lymphocyte proliferation and concentration of cytokines (IFN-γ, IL-2, IL-4, IL-10 and IL-12p70) were not significantly different between immunized and control mouse groups (p < 0.05). These data indicate that pVAX1-HSP40 induced specific immune responses and achieved a significant reduction in the number of brain cysts in Pru-infected mice, and thus can be tested in future immunization studies along with plasmids containing other immunogenic proteins as a cocktail vaccine to fully abolish chronic toxoplasmosis.